Archaeology of Babel : the colonial foundation of the humanities - Ahmed, Siraj Dean (Stanford University Press, 2018)
This book locates the origins of the modern humanities in the philological practices of late 18th-century British scholars in colonial India, offering a radical reappraisal of a range of disciplines and excavating hiddenpre-colonial practices that might well help the humanities move beyond their current methodological and political impasses.